Characterization of Hepatitis B surface Antigen gene containing recombinant Pichia pastoris - Abreshmi, Afra (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.